IMPACT OF MACULAR INTRARETINAL HEMORRHAGE AND MACULAR HOLE ON THE VISUAL PROGNOSIS OF SUBMACULAR HEMORRHAGE DUE TO RETINAL ARTERIAL MACROANEURYSM RUPTURE. Issue 4 (April 2023) - Doi, Shinichiro; Kimura, Shuhei; Saito, Shoko; Inoue, Makoto; Sakurai, Toshiya; Kobori, Akira; Hisatomi, Toshio; Imai, Hisanori; Kuriyama, Shoji; Takasu, Ippei; Hosokawa, Mio Morizane; Shiode, Yusuke; et al.
Abstract : Supplemental Digital Content is Available in the Text. Both macular intraretinal hemorrhage and macular hole were poor prognostic indicators in cases with submacular hemorrhage due to retinal arterial macroaneurysm rupture. Abstract : Purpose: To compare the effects of macular intraretinal hemorrhage (IRH) and macular hole (MH) on best-corrected visual acuity (BCVA) after displacement of submacular hemorrhage (SMH) due to retinal arterial macroaneurysm (RAM) rupture. Methods: This multicenter retrospective study included 48 eyes with SMH due to RAM rupture. Cases underwent vitrectomy to displace SMH and were followed up for 6 months. We classified cases according to the presence of IRH and MH and compared the postoperative BCVA among the groups. Results: We classified the eyes into IRH(+)MH(+) group (10 eyes), IRH(+)MH(−) group (23 eyes), and IRH(−)MH(−) group (15 eyes). The postoperative BCVA was significantly worse in the IRH(+)MH(+) and IRH(+)MH(−) groups than in the IRH(−)MH(−) group (0.91 ± 0.41 in logarithm of the minimal angle of resolution units, Snellen equivalent 20/163, 0.87 ± 0.45, 20/148, and 0.18 ± 0.21, 20/30, respectively; P < 0.001). The postoperative central retinal thickness was significantly lower in the IRH(+) group (IRH(+)MH(+) and IRH(+)MH(−) groups combined) than in the IRH(−) group (IRH(−)MH(−) group) (121.4 ± 70.1 µ m and 174.3 ± 32.9 µ m, respectively, P = 0.008). The postoperative external limiting membrane and ellipsoid zone continuities were significantly discontinuous in the IRH(+) group ( P < 0.001, P = 0.001, respectively). The multiple linear regression analysis showed that both IRH(+)MH(+) and IRH(+)MH(−) were associated with the postoperative BCVA (regression coefficient, 0.799 and 0.711, respectively; P < 0.001 for both). Conclusion: Both IRH and MH were poor prognostic indicators in cases with SMH due to RAM rupture.